2021
DOI: 10.3390/ma14237185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Behavior of Two CAD/CAM Fiber-Reinforced Composite Dental Materials by Immersion Tests

Abstract: Fiber-reinforced composites are used as restorative materials for prosthetic oral rehabilitation. Gastroesophageal reflux disease (GERD) is an accustomed affection with various oral manifestations. This study aimed to evaluate the behavior of two high-performance CAD/CAM milled reinforced composites (Trinia™, TriLor) in artificial saliva at different pH levels through immersion tests, and to determine if changes in mass or surface morphology at variable pH, specific for patients affected by GERD, appear. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 44 publications
(54 reference statements)
2
19
0
Order By: Relevance
“…32 It has been recommended for a wide range of aesthetic permanent metal-free dental prosthesis restorations on implants, including bridge frames, full-arch implant supra structures, and removable partial dentures. 33 In order to provide safe appliances for patients with particular needs who need routine magnetic resonance imaging (MRI) in the head area to monitor certain conditions like epilepsy or vascular issues, Beretta and Cirulli 34 designed a metal-free CAD-CAM device. To immediately bond to the palatal surface of the first primary molar, they used Trilor to build a Nance palatal arch space maintainer.…”
Section: Materials Used In the Fabrication Of Digitainersmentioning
confidence: 99%
“…32 It has been recommended for a wide range of aesthetic permanent metal-free dental prosthesis restorations on implants, including bridge frames, full-arch implant supra structures, and removable partial dentures. 33 In order to provide safe appliances for patients with particular needs who need routine magnetic resonance imaging (MRI) in the head area to monitor certain conditions like epilepsy or vascular issues, Beretta and Cirulli 34 designed a metal-free CAD-CAM device. To immediately bond to the palatal surface of the first primary molar, they used Trilor to build a Nance palatal arch space maintainer.…”
Section: Materials Used In the Fabrication Of Digitainersmentioning
confidence: 99%
“…Taking these things into account, F. Bechir et al [12] evaluated the behavior of two highperformance CAD/CAM milled FRC dental materials, namely Trinia and TriLor, in simulated saliva at pH values specific for patients affected by GERD, through immersion tests, in order to determine if there are any changes in terms of weight or surface morphology. The pH values of the Carter Brugirard synthetic saliva used for testing the materials were 5.7, 7.6, and a varied pH (two days immersion in pH 5.7 and one day in pH 3).…”
Section: Fiber Reinforced Composite Dental Materialsmentioning
confidence: 99%
“…The authors, who also refer to the limits of their study [12], concluded that FRC biomaterials can be seen as a suitable alternative to the metallic ones used for prosthetic frameworks, and represent a feasible alternative for the oral rehabilitation of patients suffering from GERD.…”
Section: Fiber Reinforced Composite Dental Materialsmentioning
confidence: 99%
“…Delamination, debonding, and fracture have been described as the most common clinical failure modes of FRC RBFDPs [27]. The key criteria determining the performance of FRC are fiber volume, fiber position, and fiber orientation, which have been reported through numerous load-to-failure testing [27,28].…”
Section: Introductionmentioning
confidence: 99%